Five years experience on 3, 4-diaminopyridine phosphate in Lambert–Eaton syndrome: Case reports. Issue 38 (September 2017) - Portaro, Simona; Brizzi, Teresa; Sinicropi, Stefano; Cacciola, Alberto; De Cola, Maria Cristina; Bramanti, Alessia; Milardi, Demetrio; Lupica, Antonino; Bramanti, Placido; Toscano, Antonio; Rodolico, Carmelo
Abstract: Rationale: To report our experience on 7 patients (4 males and 3 females), affected by nonparaneoplastic Lambert–Eaton myasthenic syndrome, treated with 3, 4-diaminopyridine phosphate (3, 4-DAPP) either alone or in combination with other immunosuppressants or steroids. Patient concerns: Patients have been evaluated at specific timepoints (ie, baseline and last 5 year follow-up), with neurological examination, autoantibodies against presynaptic voltage-gated Cav2.1 (P/Q type) calcium ion channel (VGCC) dosage, neurophysiological evaluation focusing on the increased amplitude of the compound muscle action potential (cMAP) after maximum voluntary effort, quantitative myasthenia gravis (QMG) and activities of daily living scales, and autonomic nervous system involvement evaluation. Outcomes: Five out of 7 patients presented a clinical improvement persisting at last 5-year follow-up; 2 out of them improved taking only 3, 4-DAPP at the maximal dosage, whereas the remaining received concomitant medications, such as prednisone and azathioprine. However, the clinical amelioration was not statistically significant. No one of the patients reported severe adverse events, except one, complaining of transient chin and perioral paresthesias. A significant association between QMG and the type of pharmacological drugs therapy ( P  = .028) emerged. Indeed, we observed an improvement of the clinical condition in all 3 subjects treated with 3, 4-DAPP and prednisone. Conclusions: In this study, we confirm 3, 4-DAPP treatment efficacy on muscle strength, but minor evidence of drug effectiveness have been demonstrated on the autonomic nervous system involvement and on the deep tendon reflexes reappearance, a part from patients who received 3, 4-DAPP associated to prednisone.